2014
DOI: 10.1007/s10096-014-2265-x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility profiles, serotype distribution and virulence determinants among invasive, non-invasive and colonizing Streptococcus agalactiae (group B streptococcus) from Malaysian patients

Abstract: A total of 103 group B streptococci (GBS) including 22 invasive, 21 non-invasive, and 60 colonizing isolates were collected in a Malaysian hospital (June 2010–October 2011). Isolates were characterized by conventional and molecular serotyping and analyzed for scpB, lmb, hylB, cylE, bac, bca and rib gene content. Antimicrobial susceptibility to penicillins, macrolides, lincosamides, quinolones and tetracyclines was determined using disk diffusion and the MICs for penicillin were determined by E-test. Molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
39
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 39 publications
(63 reference statements)
8
39
3
Order By: Relevance
“…In this study scpB, lmb, hylB, rib, bca and bac genes were detected more frequently that in studies performed by other authors [18] [51]. This could be due to the disparity in the number and kind of worked strains (our study did not include colonizing strains isolated from pregnant women).…”
Section: Discussioncontrasting
confidence: 53%
“…In this study scpB, lmb, hylB, rib, bca and bac genes were detected more frequently that in studies performed by other authors [18] [51]. This could be due to the disparity in the number and kind of worked strains (our study did not include colonizing strains isolated from pregnant women).…”
Section: Discussioncontrasting
confidence: 53%
“…Neither bac nor bca was detected in serotype Ia isolated from patients in Malaysia (Eskandarian et al . ), whereas a variety of bac and bca combinations ( bac + / bca + / bac + , bca + / bac − and bca − ) were detected in patients in Brazil (Dutra et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…The antimicrobial susceptibility testing was carried out using the antibiotics that were considered to have potential clinical utility for the prophylaxis and treatment of GBS infections and/or colonization therefore had susceptibility breakpoints recommended by the (CLSI) Guidelines 2012. The evaluated results of antibiotic susceptibility tests in this study indicated that approximately all isolated uropathogenic GBS strains were uniformly sensitive to penicillinin vitro, as different authors around the world reported it (15,16). In the reports from Iran, many studies have also shown high susceptibility of GBS isolates to Penicillin G and ampicillin; for example, Jannati et al indicated susceptibility of all GBS isolates to these antibiotics, although there is a report of high resistance (89.4%) to penicillin among uropathogenic GBS isolates by Rahbar and colleagues (17,18).…”
Section: Discussionmentioning
confidence: 56%
“…The increasing tendency in the rate of resistance to clindamycin and erythromycin among GBS strains has enhanced worry about the use of the antimicrobial agents as alternative agents for the prophylaxis or treatment of GBS infections. Plasmid-mediated resistance to antimicrobial agents has also been expected to occur in GBS and can facilitate the development of multidrug resistance (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%